P076 Active Tuberculosis Infection in Patients With Inflammatory Bowel Disease Followed in a Referral Center. (December 2019) - Lima, Camila; Garcia, Karoline; Facas, Bianca; Azevedo, Matheus; Queiroz, Natália; Barros, Luísa; Leite, André; Alexandre, Carlos; Gasparini, Rodrigo; Milani, Luciane; Sipahi, Aytan; Damião, Adérson; et al.
Abstract : BACKGROUND: Despite the decline in the incidence of Tuberculosis (TB) worldwide, this disease still causes high rates of morbimortality. It is estimated that TB caused 1.3 million deaths worldwide in 2017. Brazil is an endemic country and it counts nearly 70, 000 new cases of TB per year (1). Whether the risk of TB infection in Inflammatory Bowel Disease (IBD) patients is related to immunosuppressants or to the disease itself is controversial. This study aimed to evaluate the incidence of active TB in patients with IBD, and its relationship with immunosuppressive treatment in a tertiary referral center. METHODS: Patients with active TB were identified among 1040 IBD patients in a regular follow up at Hospital das Clínicas, São Paulo, Brazil, from 2010 to 2017. Data regarding disease phenotype, IBD treatment at the time of TB diagnosis and the previous status of TB screening was retrospectively collected from electronic medical records. The diagnosis of active TB was based on symptoms, tuberculin skin test (TST), sample cultures, images, and endoscopic exams. RESULTS: Twenty-three patients with active TB were identified (mean age at TB diagnosis 49 [28–69]; 13/23 [56.5%] female). The person-time incidence rate of active TB was 2.21 cases/100 inhabitants/year in our IBD population. The relative risk of active TB was increased (RR 6.6) compared to general Brazilian population. Fifteen patients (65.2%) had Crohn's Disease (7 perianal; 4 stricturing; 4 non-penetrating non-stricturing) and eight (34.7%) had Ulcerative Colitis (7 extensive disease). Regarding IBD treatment, 13/23 (56.5%) patients were under anti-TNF drugs (9 Infliximab; 4 Adalimumab), six of them (46.1%) in monotherapy and seven (53.8%) under combotherapy with thiopurines. Five patients (21.7%), were under AZA monotherapy and one was under steroids. Regarding the interval between anti-TNF use and TB diagnosis, just one case was diagnosed in the first 6 months of treatment. Most patients (14/19; 73.6%) developed active TB after 24 months of exposition to immunosuppressant medications; two (2/19; 10.5%) between 12–24 months of exposure and three (3/19; 15.7%) between 6–12 months. All four of the patients (4/23; 17.4%) that were not under immunosuppressant drugs were smokers, one of them was also an alcoholic and another one treated active TB seven years before the reinfection. The most common TB site was pulmonary (16/23, 69.5%) and no deaths resulted from active TB. One case of TB occurred three years after isoniazid chemoprophylaxis for latent TB in a patient under combotherapy (anti-TNF and AZA). CONCLUSION(S): Our patients presented an incidence of TB higher than the general population in Brazil. Immunosuppressive drugs seem to be a major causal factor, especially anti-TNF. Most cases occurred after the first six months of treatment suggesting a new infection. This study reinforced the importance of an accurate screening for TB at IBD diagnosis and prior to initiation of immunosuppressive therapy. Appropriate follow-up is required in immunosuppressed patients living in endemic areas for TB.